2013
DOI: 10.1111/j.1937-5956.2012.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Advance Selling in the Presence of Speculators and Forward‐Looking Consumers

Abstract: This article examines the pricing policy of a monopolist seller who may sell in advance of consumption in a market that comprises of myopic consumers, forward‐looking consumers, and speculators. The latter group has no consumption value for the goods and is in the market with the sole objective of making a profit by reselling the purchased goods shortly after. Consumers, although homogeneous in terms of their valuations, are different with respect to their perspectives. We show that in an “upward” market where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Consumers' utilities are uncertain in the AS period because there is little information about the product at this time, and it is assumed that all consumers are homogeneous, and informed consumers have the same expected valuation for the product when it is time to pay the deposit (Cachon & Feldman, 2017; Lim & Tang, 2013; Zhao et al, 2016). Because the deposit will not be returned if a consumer regrets paying it, consumers might feel loss of the deposit.…”
Section: Basic Modelmentioning
confidence: 99%
“…Consumers' utilities are uncertain in the AS period because there is little information about the product at this time, and it is assumed that all consumers are homogeneous, and informed consumers have the same expected valuation for the product when it is time to pay the deposit (Cachon & Feldman, 2017; Lim & Tang, 2013; Zhao et al, 2016). Because the deposit will not be returned if a consumer regrets paying it, consumers might feel loss of the deposit.…”
Section: Basic Modelmentioning
confidence: 99%
“…Li et al [13] investigate the advance selling price strategies for oligopolists when considering the effect of product diffusion and the competitive market. Further, some researchers consider the fact that advance selling with price discrimination can lead to strategic consumer behavior, e.g., Fay and Xie [1]; Li and Zhang [3]; Lim and Tang [14]; Yu et al [15].…”
Section: Advance Selling: Improving Demand Forecasting Andmentioning
confidence: 99%
“…Forward-looking consumers take future prices and valuations into consideration in making their decisions [44]. Sun et al [57] showed that excluding the forward-looking behavior leads to overestimation of promotion elasticity.…”
Section: Forward-looking Consumersmentioning
confidence: 99%